STUDI FAKTOR RISIKO OSTEOPOROSIS PADA PEREMPUAN PRA-LANSIA DI KELURAHAN CURUG, KECAMATAN CIMANGGIS, KOTA DEPOK, JAWA BARAT - Ruben Almando Panjaitan (2023)
Background: It is estimated that by 2050 the number of cases of hip fracture due to osteoporosis in Asia will increase 2.28 times from 2018. It is important for screening in women over 45 years to prevent osteoporosis and bone fractures. Many study have investigated osteoporosis risk factors, but few have specifically addressed osteoporosis risk factors in middle-age women with the age of 45 - 59th years old. Objective: to determine the relationship between osteoporosis risk factors and the incidence of osteoporosis in middle-age women in Cimanggis District. Methods: A cross-sectional and consecutive sampling method were conducted on 113 participants. Bone density was evaluated with BMD Osteosys Sonost 3000 and Risk Factor was evaluated questionnaire International Osteoporosis Foundation (IOF). Result: Among 113 respondents obtained that 7 respondent (6,2%) had normal bone density and 106 respondent (93,8%) had low bone density. Height loss, family history of hip fracture, history of fracture, alcohol consumption, smoking habit, BMI <18,5, History of long-term drug consumption, comorbid disease was not significantly associated with bone density. Conlusion: Special attention was needed for middle-age women to identify risk factors of osteoporosis that can affect the course of the disease. Kata Kunci: Osteoporosis, Risk Factor, Middle-age, Women, BMD